Strategy for Program Socialization and Fund Utilization by PNM Participants - Nurhalizah, Irma; Ismaniar, Ismaniar (Universitas Negeri Padang, 2025)
This research is motivated by the phenomenon of low utilization of PNM funds by participants in accordance with program regulations. This study aims to analyze program socialization strategies that can be implemented to support fund utilization by PNM participants in accordance with regulations. The method used in this research is a literature study, which involves reviewing various sources such as scientific journals, books, and previous research relevant to the topic. The topic analyzed in this study is the low utilization of funds by PNM participants according to program regulations. The research results show that; (1) the phenomenon of the use of PNM funds that occurred was not in accordance with program provisions. For example, most of the funds were not used for business capital but for daily consumption purposes. (2) socialization strategy for the use of PNM funds. The socialization strategies implemented include; a participatory approach through officers, financial literacy training and education, ongoing mentoring and monitoring, use of socialization media, a group approach (joint responsibility), and the implementation of an incentive and sanction system. So, it can be concluded that the majority of PNM funds are used not for working capital or business development, but rather for daily consumption needs. Program socialization strategies are crucial to ensuring that PNM funds are utilized in accordance with program regulations. This research is expected to provide guidance for program managers to strengthen socialization aspects to ensure more productive and sustainable fund utilization.